Transformation of Higher Education During the Pandemic: Pain Points - I. R. Gafurov; H. I. Ibragimov; A. M. Kalimullin; T. B. Alishev (Moscow Polytechnic University, 2020)
The relevance of the study is due to the contradiction between the mass transition of the Russian system of higher education to the distance learning format and the insufficient willingness of participants in the educational process to work under the new requirements caused by the COVID 19 pandemic. Teachers, students and administrators of higher educational institutions in Russia have encountered a number of difficulties. Their analysis will highlight the objective and subjective factors of their occurrence and develop recommendations for the further organization of distance learning in its combination with the traditional format. The purpose of the study was to analyze the modern work experience in the remote format of one of the leading Russian universities - Kazan Federal University. On this basis, the article analyzes successes and problems of this process, shows the contradictions between traditional and distance learning, considers the main models of educational organization that involve traditional and remote learning formats using distance educational technologies. It is concluded that in the system of basic formal education at all levels and areas of training, distance learning can be considered as a form that complements and strengthens the social, pedagogical, organizational, psychological, and didactic potential of the traditional (face-to-face) educational format.The work comprehensively used the methods of theoretical (analysis, synthesis, systematization, comparison, etc.) and empirical (study of literature, conversation, questioning, observation) research.